2011
DOI: 10.3109/09513590.2011.631628
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ghrelin and its receptors in ovarian endometrioma

Abstract: Endometriosis is a common gynaecological disorder manifesting by implantation and growth of endometrial tissue outside the uterine cavity. The evidence accumulates that endometriosis may be associated with abrogated regulation of energy balance. Ghrelin is one of the most important orexigenic factor which may also play a role in regulation of inflammatory and angiogenic reactions. The present study was aimed at investigating expression profile of ghrelin and its receptors (GHSR1α and GHSR1β) in endometriotic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The GHSR is a typical G protein-coupled seven-transmembrane receptor ( 15 ). Several studies have identified the protective effects of ghrelin ( 4 , 16 17 18 ), but little is known about the effects of ghrelin on ovarian cancer cells or their mechanism of action. We found that the mechanism through which ghrelin inhibits the growth of HO-8910 cells involves the ERK1/2 branch of MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GHSR is a typical G protein-coupled seven-transmembrane receptor ( 15 ). Several studies have identified the protective effects of ghrelin ( 4 , 16 17 18 ), but little is known about the effects of ghrelin on ovarian cancer cells or their mechanism of action. We found that the mechanism through which ghrelin inhibits the growth of HO-8910 cells involves the ERK1/2 branch of MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the overall five-year survival for all women diagnosed with epithelial ovarian carcinoma is only 44% ( 2 , 3 ). Because of the overall high mortality of ovarian cancer, women at increased risk may be counseled to undergo prophylactic (and possibly unnecessary) oophorectomy ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Milewski et al have recently shown that ghrelin/GHS-R1a are expressed both in glandular endometrioid epithelium and in some stromal cells, particularly in some fibroblasts, blood vessels and infiltrating leukocytes in ovarian endometrioma. 26 Based on their results, they speculated that co-localization of ghrelin/GHS-R1a affects the development and growth of endometriotic lesions and influences local inflammatory and angiogenic responses. In the present study, we also detected high expression of ghrelin/GHS-R1a in tumor cells and proliferating microvessels of AAs and GBs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its limitations due to a relatively low sample size, this was the first study to suggest a role of ghrelin in the pathophysiology of endometriosis. A few years later, the same investigators studied the expression of ghrelin and the localization of its GHSR1a receptor in endometriotic tissue samples from 20 women [ 53 ]. They found high expression of both ghrelin and its receptor in endometrioid glandular epithelium, as well as in the endothelium of stromal blood vessels of the same tissue and in leukocytes isolated from the peritoneal fluid.…”
Section: Metabolic Surgery What It Is and How It Can Contribute To Endometriosis Researchmentioning
confidence: 99%